RELIABILITY ANALYSIS OF THE PRESSURE STEAM STERILIZER BASED ON MPGW DISTRIBUTION - ZHONG TianPing (Jixie qiangdu)
The hazard rate function with a bathtub-shaped curve is crucial in reliability engineering due to its ability to capture certain observed failure rate characteristies in real-world scenarios. This study introduces a novel MPGW (Modified Power Generalized Weibull) distribution capable of modeling hazard rate function exhibiting a bathtub shape. To evaluate the effectiveness of this model, the study conducted empirical research using a dataset of pressure steam sterilizer failures and compared its performance to 5 classical distribution models, the results indicated that this model exhibits significant advantages in terms of flexibility.